2006
DOI: 10.1007/bf02969416
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anticonvulsant activities ofN-Cbz-α-aminoglutarimidooxy carboxylate derivatives

Abstract: Previous studies on the anticonvulsant activity of N-Cbz-alpha-aminoglutarimides have shown that the derivatives of N-Cbz-alpha-amino-N-alkoxy glutarimide have significant anticonvulsant activity. In addition, their anticonvulsant activities are dependent on the presence of N-alkoxy groups. Based on these results, a series of N-Cbz-alpha-amino-glutarimidooxy carboxylates derivatives (3a-e) were synthesized in moderate yield using a known synthetic procedure. Their anticonvulsant activities were evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…1, were reported to exhibit moderate anticonvulsant activities. (Byun et al, 2006;Jung et al, 1998;Kim et al, 2004;Lee et al, 1997Lee et al, , 1999Son et al, 1998) Some of them showed comparable anticonvulsant activities in both of the MES and PTZ tests enough to be recommended as broad spectrum anticonvulsant drug candidates. Kim et al, 2004;Lee et al, 1997Lee et al, , 1999 As seen in Fig.…”
Section: Introductionmentioning
confidence: 96%
“…1, were reported to exhibit moderate anticonvulsant activities. (Byun et al, 2006;Jung et al, 1998;Kim et al, 2004;Lee et al, 1997Lee et al, , 1999Son et al, 1998) Some of them showed comparable anticonvulsant activities in both of the MES and PTZ tests enough to be recommended as broad spectrum anticonvulsant drug candidates. Kim et al, 2004;Lee et al, 1997Lee et al, , 1999 As seen in Fig.…”
Section: Introductionmentioning
confidence: 96%
“…We previously identified a family of novel anticonvulsants, the N-Cbz-α-aminoglutarimidooxy carboxylate derivatives (Byun et al, 2006;Jung et al, 1998;Kim et al, 2004;Lee et al, 1997;Lee et al, 1999;Son et al, 1998) These compounds can affect the central nervous system (CNS) and have a cyclic imide group (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%